The Effect of Public Investment on the Cycle and Economic Growth: A Simple Theoretical Model - Velázquez-Orihuela, Daniel; Vargas-Sánchez, Juan-Roberto; Hernández-Veleros, Zeus Salvador (International Journal of Economics and Financial Issues, 2019)
In the specialized literature, there are two versions of the effect of public investment on growth. One of them states that the relationship between them is positive; the other states that there is optimal public investment. This paper proposes an analytical theoretical scheme supporting that, in the short term, the relationship between public investment and economic growth is positive. However, in the long term, this relationship can still be positive or become negative depending on whether there is a crowding-out or a crowding-in effect. Whenever a crowding-in effect occurs, and the government does not have to decrease its investment, it does not increase debt or taxes, and the economy will be on a growth path. However, if there is a crowding-out effect, the trajectory of the economy will depend on the productive efficiency of the displaced capital. Keywords: public investment, economic cycle, economic growth, crowding-in, crowding-out. JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.7237